Modified carbon fiber, carbon fiber reinforced composite coating and preparation method and application thereof
By constructing zinc oxide seed layer and micro-nano structure on the surface of carbon fiber and performing functional treatment, the interface combination between carbon fiber and resin is solved, and the interface failure problem of carbon fiber reinforced composite materials in harsh marine environments is significantly improved. The material's resistance is significantly improved Erosion and wear resistance.
Patent Information
- Application Number
- CN202411418674.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The existing carbon fiber reinforced composite materials have serious interface failure problems in harsh marine environments, resulting in poor interface bonding strength and difficult to meet the needs of high erosion resistance.
The zinc oxide seed layer and micro-nano structure are constructed in situ on the surface of the carbon fiber by hydrothermal method, and the interface bond between the carbon fiber and the resin is enhanced by functionalization of the silane coupling agent, forming mechanical interlocking and chemical bonding.
It significantly improves the interface performance of carbon fiber reinforced composite materials, reduces erosion quality and wear rate, and improves anti-friction wear and erosion resistance.
Smart Images

Figure CN119308134A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon fiber reinforced composite materials for marine environment service, and specifically relates to a modified carbon fiber, a carbon fiber reinforced composite coating, and a preparation method and application thereof. Background Art
[0002] Offshore docks and pilot stations, offshore wind power equipment, bridge construction and other marine equipment or projects have been in the typical marine "four highs environment" of high humidity, high heat, high salt fog and high ultraviolet rays for a long time, and under the influence of factors such as saturated oxygen and marine microorganisms, the corrosion rate of materials has been accelerated, their service life has been shortened, and even huge safety hazards have been created. In different areas of the ocean, the splash zone is a typical strong corrosion damage area in the marine environment due to the coupling of multiple factors such as strong ultraviolet rays, high oxygen content, alternating dry and wet seawater, seawater scouring and sediment erosion in the environment. The degree of corrosion is 5-10 times that of the full immersion area in the ocean.
[0003] Among the many protective methods, organic protective coatings are widely used due to their low cost, simple process, corrosion resistance and other advantages. However, due to the fact that it is easy to form defects such as pores and cracks during the curing process, as well as its poor mechanical properties, it is difficult to meet the service requirements of high-erosion resistance protective materials in the harsh service environment of the splash zone. Carbon fiber and its composite materials are widely used in aerospace, military, rail transportation and other fields due to their excellent mechanical properties, heat resistance, corrosion resistance, impact resistance and other properties. The fiber-reinforced composite material prepared by adding carbon fiber as a filler to the epoxy resin matrix has better mechanical properties, designability and better corrosion resistance, and is a very potential means to solve the corrosion problem of metal materials in the splash zone. However, due to the shortcomings of the smooth surface and low chemical activity of carbon fiber, the interface wettability of the carbon fiber resin composite coating is poor, the bonding force between the fiber and the resin matrix is also weak, and the interface bonding strength is poor. The interface failure problem of carbon fiber reinforced composite coatings in harsh marine environments is the key to its long-life safe service. Therefore, the construction of carbon fiber composite materials with synergistic enhancement of interface meshing and chemical bonding is an important development trend at present. At present, most of the research can improve the interface performance of composite materials to a certain extent through simple surface modification or constructing an interface layer on the fiber surface through sizing agents. However, due to the single modification mechanism and weak modification effect, the improvement of interface performance is limited.
[0004] Zinc oxide micro-nanostructures can not only grow zinc oxide nanoparticles, nanowires, and nanoflower-like morphologies on the fiber surface, but also the preparation conditions of nano zinc oxide are mild and the process is simple. It is widely used in the modification of various fiber surfaces and has achieved remarkable results. However, most researchers simply grow zinc oxide structures on the fiber surface. The zinc oxide structures grown on the fiber are sparse and unevenly distributed, resulting in poor interface bonding between the fiber and the resin, and easy peeling between the resin and the carbon fiber. How to improve the uneven growth of zinc oxide structures on the carbon fiber surface and the interface bonding strength between the carbon fiber and the resin on this basis, and then design a strong interface bonding type carbon fiber reinforced composite material to meet its excellent mechanical properties, wear resistance and erosion resistance requirements in the harsh marine environment. Summary of the invention
[0005] The main purpose of the present invention is to provide a modified carbon fiber, a carbon fiber reinforced composite coating and a preparation method and application thereof, so as to overcome the deficiencies of the prior art.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0007] An embodiment of the present invention provides a method for preparing modified carbon fiber, which comprises:
[0008] A zinc oxide seed layer and a zinc oxide micro-nano structure were sequentially constructed in situ on the surface of carbon fiber by a hydrothermal method to obtain a carbon fiber with a zinc oxide micro-nano structure.
[0009] And, a silane coupling agent is used to perform surface functionalization treatment on the carbon fiber with zinc oxide micro-nano structure to obtain modified carbon fiber.
[0010] The embodiment of the present invention also provides modified carbon fiber prepared by the aforementioned preparation method.
[0011] The embodiment of the present invention further provides a carbon fiber reinforced composite coating, which is obtained by mixing the aforementioned modified fiber, epoxy resin and curing agent and applying the mixture to the surface of a substrate for curing.
[0012] The embodiment of the present invention further provides a carbon fiber reinforced composite material, which is obtained by mixing the aforementioned modified fiber, epoxy resin and curing agent and performing a curing treatment.
[0013] The embodiments of the present invention also provide use of the aforementioned modified carbon fiber, carbon fiber reinforced composite coating or carbon fiber reinforced composite material in preparing materials for service in marine environments.
[0014] Compared with the prior art, the present invention has the following beneficial effects:
[0015] (1) The dense zinc oxide micro-nano structure on the surface of the carbon fiber in the present invention is first treated with a zinc oxide seed solution to grow a zinc oxide seed layer on the surface of the carbon fiber, providing active sites for the subsequent growth of the zinc oxide micro-nano structure, and then the dense zinc oxide micro-nano structure is efficiently grown in situ on the surface of the carbon fiber by a hydrothermal method;
[0016] (2) The interfacial mechanical interlocking effect in the carbon fiber reinforced composite material of the present invention is to increase the surface roughness of the carbon fiber by pre-growing a zinc oxide seed layer on the carbon fiber surface and then in-situ growing a zinc oxide micro-nano structure, so that the interfacial bonding strength between the carbon fiber and the resin is improved, forming a strong mechanical meshing effect;
[0017] (3) The present invention forms a chemical bond at the interface between the carbon fiber and the resin through surface functionalization treatment, and further performs surface chemical grafting modification to introduce amino groups on the basis of the growth of zinc oxide micro-nanostructure on the surface of the carbon fiber, so that a strong chemical bond can be formed between the carbon fiber and the resin. Under the dual effects of mechanical interlocking and chemical bonding, the interface bonding strength and interface stress transfer can be effectively improved;
[0018] (4) The mechanical interlocking effect and chemical bonding strengthening synergistic effect of the carbon fiber reinforced composite material in the present invention significantly improve the interface performance of the carbon fiber reinforced composite material, and its erosion mass is reduced by 25%, the erosion volume is reduced by 20%, and the wear rate is reduced by 45%;
[0019] (5) The method provided by the present invention is suitable for improving the interface properties of carbon fiber composite materials, thereby improving the friction and wear resistance and erosion resistance of fiber-reinforced composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 is a SEM image of the carbon fiber growing the interface reinforcement phase in Example 1 of the present invention;
[0022] Figure 2 is a morphology diagram of the interface between carbon fiber and resin of the carbon fiber reinforced composite material in Example 1 of the present invention after an erosion test;
[0023] Figure 3 is a SEM image of the carbon fiber growing the interface reinforcement phase in Example 2 of the present invention;
[0024] Figure 4 is a morphology diagram of the interface between carbon fiber and resin of the carbon fiber reinforced composite material in Example 2 of the present invention after an erosion test;
[0025] Figure 5 is a SEM image of the carbon fiber growing the interface reinforcement phase in Comparative Example 1 of the present invention;
[0026] Figure 6 is a morphology diagram of the interface between carbon fiber and resin of the carbon fiber reinforced composite material in Comparative Example 1 of the present invention after an erosion test;
[0027] Figure 7 is a SEM image of the carbon fiber growing the interface reinforcement phase in Comparative Example 2 of the present invention;
[0028] Figure 8 is a morphology diagram of the interface between carbon fiber and resin of the carbon fiber reinforced composite material in Comparative Example 2 of the present invention after an erosion test;
[0029] Fig. 9 is a SEM image of the carbon fiber growing the interface reinforcement phase in Comparative Example 3 of the present invention;
[0030] Fig.10 is a morphology diagram of the interface between carbon fiber and resin of the carbon fiber reinforced composite material in Comparative Example 3 of the present invention after erosion test;
[0031] Fig.11 is a SEM image of the carbon fiber growing the interface reinforcement phase in Comparative Example 4 of the present invention;
[0032] Fig.12 is a morphology diagram of the interface between carbon fiber and resin of the carbon fiber reinforced composite material in Comparative Example 3 of the present invention after erosion test;
[0033] Fig.13 It is a friction test wear rate data diagram of the composite materials in Examples 1-2 of the present invention and Comparative Examples 1-4;
[0034] Fig.14 is a graph showing mass loss data of erosion tests of the composite materials in Examples 1-2 of the present invention and Comparative Examples 1-4;
[0035] Fig.15 It is a volume loss data diagram of the erosion test of the composite materials in Examples 1-2 of the present invention and Comparative Examples 1-4. DETAILED DESCRIPTION
[0036] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Specifically, as one aspect of the technical solution of the present invention, a method for preparing a modified carbon fiber includes:
[0038] A zinc oxide seed layer and a zinc oxide micro-nano structure were sequentially constructed in situ on the surface of carbon fiber by a hydrothermal method to obtain a carbon fiber with a zinc oxide micro-nano structure.
[0039] And, a silane coupling agent is used to perform surface functionalization treatment on the carbon fiber with zinc oxide micro-nano structure to obtain modified carbon fiber.
[0040] In some preferred embodiments, the preparation method specifically comprises:
[0041] (1) subjecting a first mixed reaction system comprising at least carbon fiber, an alkaline substance, and a zinc salt to a hydrothermal reaction, cooling the system to room temperature, and then heating the system to repeat the hydrothermal reaction and cooling operations to obtain a carbon fiber having a surface growth seed layer;
[0042] (2) subjecting a second mixed reaction system comprising at least the carbon fiber of the surface growth seed layer, an organic ammonium salt, and a zinc salt to a hydrothermal reaction to obtain a carbon fiber having a zinc oxide micro-nano structure;
[0043] (3) placing the carbon fiber having the zinc oxide micro-nano structure in a mixed solution comprising a silane coupling agent and a solvent for functionalization treatment to obtain a modified carbon fiber.
[0044] Furthermore, the carbon fiber includes any one or more combinations of carbon fiber powder, chopped carbon fiber, and carbon fiber cloth, but is not limited thereto.
[0045] Further, the alkaline substance includes sodium hydroxide and / or ammonia water, but is not limited thereto.
[0046] Furthermore, the zinc salt in step (1) includes any one or more combinations of zinc sulfate, zinc acetate dihydrate, zinc nitrate, and zinc chloride, but is not limited thereto.
[0047] Furthermore, in step (1), the mass ratio of the alkaline substance to the zinc salt is 1:(1.8-2.5).
[0048] Furthermore, the process parameters adopted for the hydrothermal reaction in step (1) include: temperature of 120-150° C., reaction time of 8-14 h, and stirring speed of 100-300 rpm.
[0049] Furthermore, the heating, hydrothermal reaction and cooling operations in step (1) are repeated 2 to 5 times.
[0050] In some preferred embodiments, step (2) specifically comprises:
[0051] The carbon fiber and zinc salt of the surface growth seed layer obtained in step (1) are mixed with water, and heated to dissolve and disperse at a stirring speed of 500 to 1000 rpm and a temperature of 40 to 65° C. to form a carbon fiber / zinc salt dispersion, and ammonia water is used to adjust the pH value of the carbon fiber / zinc salt solution to 7.5 to 9.0;
[0052] Mixing an organic ammonium salt with water, and heating and dissolving them at a stirring speed of 500 to 1000 rpm and a temperature of 40 to 65° C. to form an organic ammonium salt solution;
[0053] Furthermore, the organic ammonium salt solution is mixed with the carbon fiber / zinc salt dispersion and reacted at 120-150° C. for 10-14 hours, and then dried to obtain the carbon fiber with zinc oxide micro-nano structure.
[0054] Furthermore, the mass volume ratio of the carbon fiber, zinc salt and water in the surface growth seed layer is (0.2-0.5) g: (0.29-0.33) g: 20 mL.
[0055] Furthermore, the concentration of the ammonia water is 2-10 wt %.
[0056] Furthermore, the mass ratio of the organic ammonium salt to water is (0.0001-0.0003):1.
[0057] Furthermore, the volume ratio of the organic ammonium salt solution to the carbon fiber / zinc salt dispersion is (0.5-1.5):1.
[0058] Furthermore, the drying process is carried out at a temperature of 60 to 90° C. and for a time of 8 to 12 hours.
[0059] Furthermore, the zinc salt in step (2) includes any one or more combinations of zinc nitrate, zinc chloride, and zinc acetate, but is not limited thereto.
[0060] Further, the organic ammonium salt includes any one or more combinations of cetyltrimethylammonium bromide, tetraethylammonium sulfate, cetyltrimethylammonium fluoride, and alanine dimethylamine salt, but is not limited thereto.
[0061] In some preferred embodiments, step (3) specifically includes: mixing a silane coupling agent, a solvent, and water, then adding carbon fiber having a zinc oxide micro-nano structure and reacting for 8 to 15 hours at a stirring speed of 500 to 800 rpm and a temperature of 60 to 80°C, and then washing and drying to obtain modified carbon fiber.
[0062] Furthermore, the volume ratio of the silane coupling agent, anhydrous ethanol and water is 23:(200-400):(1-5).
[0063] Further, the solvent includes anhydrous ethanol, but is not limited thereto.
[0064] Further, the silane coupling agent includes any one or more combinations of N-β-aminoethyl-γ-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-propylaminomethoxymethylsilane, and 3-aminopropyltriethoxysilane, but is not limited thereto.
[0065] Furthermore, the washing treatment includes: washing with anhydrous ethanol for 3 to 5 times.
[0066] Furthermore, the drying process is carried out at a temperature of 60 to 90° C. and for a time of 8 to 12 hours.
[0067] In some preferred embodiments, the preparation method further comprises: pre-treating the carbon fiber first; the pre-treatment at least comprises degreasing, desizing, and oxidation treatment.
[0068] In some more specific embodiments, the method for preparing the modified carbon fiber comprises the following steps:
[0069] (1) Pre-growth of a seed layer on the surface of carbon fiber: adding the pre-treated carbon fiber to a mixture of sodium hydroxide and zinc salt for hydrothermal reaction, and cooling to room temperature; heating again for hydrothermal reaction, and cooling to room temperature to obtain a carbon fiber with a zinc oxide seed layer grown on the surface;
[0070] (2) Growth of zinc oxide micro-nanostructure on the surface of carbon fiber: putting the carbon fiber with the surface-grown zinc oxide seed layer obtained in step (1) into a mixed solution of organic ammonium salt and zinc salt for hydrothermal reaction, taking out, and drying to obtain a carbon fiber with grown zinc oxide micro-nanostructure, i.e., a carbon fiber with zinc oxide micro-nanostructure;
[0071] (3) Surface functionalization of carbon fiber: The carbon fiber with the zinc oxide micro-nano structure obtained in step (2) is immersed in a mixed solution of a silane coupling agent and ethanol for reaction, and then taken out, washed, and dried to obtain a modified carbon fiber with surface grafted silanol.
[0072] (4) Evenly mixing the modified carbon fiber obtained in step (3) with a resin and curing the mixture to obtain an interface-reinforced carbon fiber reinforced composite material.
[0073] Preferably, the carbon fiber in step (1) includes, but is not limited to, carbon fiber products in the form of carbon fiber powder, chopped carbon fiber, carbon fiber cloth, etc.
[0074] Preferably, the zinc salt in step (1) is one or more of zinc sulfate, zinc acetate dihydrate, zinc nitrate, and zinc chloride; the mass ratio of sodium hydroxide to zinc salt in the mixed solution of sodium hydroxide and zinc salt is 1:(1.8-2.5); the reaction temperature of adding the pre-treated carbon fiber to the sodium hydroxide and zinc salt solution is 120-150° C., the reaction time is 8-14 h, and the stirring speed is 100-300 rpm; the step (1) also includes: repeating the step of "heating again for hydrothermal reaction and cooling to room temperature" for a total of 2-5 times.
[0075] Preferably, the reaction step of growing zinc oxide micro-nano on the surface of carbon fiber in step (2) comprises: mixing the carbon fiber obtained in step (1) and the zinc salt in 20 mL of deionized water in a mass ratio of (0.2-0.5): (0.29-0.33), heating and dissolving at a stirring speed of 500-1000 rpm and 40-65° C. to obtain a carbon fiber / zinc salt solution; adjusting the pH of the carbon fiber / zinc salt solution to (7.5-9.0) by ammonia water, wherein the ammonia water concentration is (2-10 wt %); mixing an organic ammonium salt and deionized water in a mass ratio of 0.00025:1, heating and dissolving at a stirring speed of 500-1000 rpm and 40-65° C. to obtain an organic ammonium salt solution; adding an equal volume of the obtained organic ammonium salt solution to the carbon fiber / zinc salt solution, reacting at 120-150° C. for 10-14 h, and drying in an oven at 60-90° C. for 8-12 h to obtain a carbon fiber with a zinc oxide micro-nano structure.
[0076] Preferably, in step (2), the ammonium salt is one or more of cetyltrimethylammonium bromide, tetraethylammonium sulfate, cetyltrimethylammonium fluoride, and alanine dimethylamine salt, and the zinc salt is one or more of zinc nitrate, zinc chloride, or zinc acetate.
[0077] Preferably, the silane coupling agent in step (3) is one or more of N-β-aminoethyl-γ-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-propylaminomethoxymethylsilane, and 3-aminopropyltriethoxysilane; the step of functionalizing the surface of the carbon fiber comprises: mixing the silane coupling agent and anhydrous ethanol in a volume ratio of 23:(200-400), adding 1-5 mL of deionized water to react, taking out, washing, and drying to obtain a modified carbon fiber with surface grafted silanol.
[0078] Preferably, in step (3), the reaction temperature is 60-80° C., the reaction time is 8-15 h, and the stirring speed is 500-800 rpm.
[0079] Preferably, the washing in step (3) is performed by washing with anhydrous ethanol for 3 to 5 times, and the drying is performed in an oven at 60 to 90° C. for 8 to 12 hours.
[0080] Preferably, the specific steps of the pre-treatment include: immersing the carbon fiber in a sodium hydroxide solution with a concentration of 5 to 10 wt%, treating it for 6 to 10 hours at a temperature of 60 to 80° C. and a stirring speed of 300 to 800 rpm, and rinsing it with deionized water for 3 to 5 times; then immersing the treated carbon fiber in acetone, treating it for 4 to 8 hours at a temperature of 40 to 70° C. and a stirring speed of 300 to 800 rpm, rinsing it with deionized water for 3 to 5 times, and then drying it in an oven at 40 to 90° C. for 6 to 12 hours to obtain desizing carbon fiber; finally, immersing the desizing carbon fiber in a nitric acid solution with a concentration of 30 to 60 wt%, treating it for 6 to 10 hours at a temperature of 60 to 90° C. and a stirring speed of 300 to 800 rpm, and rinsing it with deionized water for 3 to 5 times to obtain oxidized carbon fiber, i.e., carbon fiber after pre-treatment; wherein the pre-treatment at least causes the surface of the obtained carbon fiber to contain hydroxyl and / or carboxyl functional groups.
[0081] Preferably, in step (4), the modified carbon fiber and the resin are stirred at a speed of 600 to 3500 rpm and for a stirring time of 5 to 8 min.
[0082] Preferably, in step (4), the curing temperature of the interface-reinforced carbon fiber composite material is 25 to 80° C. in three-stage temperature-raising curing, and the total curing time is 12 to 24 hours.
[0083] Another aspect of the embodiments of the present invention further provides modified carbon fiber prepared by the aforementioned preparation method.
[0084] Another aspect of the embodiments of the present invention further provides a carbon fiber reinforced composite coating, wherein the carbon fiber reinforced composite coating is obtained by mixing the aforementioned modified fiber, epoxy resin and curing agent and applying the mixture to the surface of a substrate for curing.
[0085] Furthermore, the epoxy resin includes any one or more combinations of epoxy E51, epoxy E44, and epoxy E38, but is not limited thereto.
[0086] Furthermore, the curing agent includes 1618 epoxy curing agent, but is not limited thereto.
[0087] Furthermore, the curing temperature is 25 to 80° C., the curing is performed in three stages, and the total curing time is 12 to 24 hours.
[0088] Another aspect of the embodiments of the present invention further provides a carbon fiber reinforced composite material, wherein the carbon fiber reinforced composite material is obtained by mixing the aforementioned modified fiber, epoxy resin and curing agent and performing a curing treatment.
[0089] Furthermore, the curing temperature is 25 to 80° C., the curing is performed in three stages, and the total curing time is 12 to 24 hours.
[0090] Furthermore, the epoxy resin includes any one or more combinations of epoxy E51, epoxy E44, and epoxy E38, but is not limited thereto.
[0091] Furthermore, the curing agent includes 1618 epoxy curing agent, but is not limited thereto.
[0092] Another aspect of the embodiments of the present invention further provides use of the aforementioned modified carbon fiber, carbon fiber reinforced composite coating or carbon fiber reinforced composite material in preparing materials for service in harsh marine environments.
[0093] The invention has the following advantages: mild conditions and simple process; the bonding strength between the interface reinforcement phase carbon fiber and the resin is significantly improved; the interface performance between the modified fiber and the resin and the erosion resistance are significantly enhanced; compared with the unmodified carbon fiber, the wear rate of the modified carbon fiber is reduced by 10% to 50% after the friction and wear test, and the mass loss of the prepared carbon fiber reinforced composite coating is reduced by 18% to 25% and the volume loss is reduced by 10% to 20% after the erosion test.
[0094] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0095] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0096] The following examples and comparative examples pre-treat carbon fibers including the following steps:
[0097] The carbon fiber is immersed in a sodium hydroxide solution with a concentration of 19wt%, treated at a temperature of 80°C and a stirring speed of 800rpm for 6h, and rinsed with deionized water 5 times; then the treated carbon fiber is immersed in acetone, treated at a temperature of 70°C and a stirring speed of 800rpm for 8h, rinsed with deionized water 5 times, and then dried in an oven at 80°C for 12h to obtain desizing carbon fiber; finally, the desizing carbon fiber is immersed in a nitric acid solution with a concentration of 37wt%, treated at a temperature of 85°C and a stirring speed of 800rpm for 6h, and rinsed with deionized water 5 times to obtain oxidized carbon fiber, i.e., carbon fiber after pretreatment; wherein the pretreatment at least makes the surface of the obtained carbon fiber contain hydroxyl and / or carboxyl functional groups.
[0098] Example 1
[0099] (1): Pre-growth of seed layer on carbon fiber surface: Add the pre-treated carbon fiber powder to a mixture of sodium hydroxide and zinc acetate dihydrate (the mass ratio of sodium hydroxide to zinc acetate dihydrate is 1:1.8), perform hydrothermal reaction for 14 hours at a stirring speed of 300 rpm and a temperature of 150°C, and cool to room temperature; repeat the step of "heating again for hydrothermal reaction and cooling to room temperature" for a total of 3 times to obtain a carbon fiber with a zinc oxide seed layer grown on the surface;
[0100] (2): Growth of zinc oxide micro-nanostructure on the surface of carbon fiber: The carbon fiber with the surface grown zinc oxide seed layer obtained in step (1) and zinc nitrate hexahydrate are mixed in 20 mL of deionized water at a mass ratio of 0.2:0.29, and heated to dissolve and disperse at a stirring speed of 1000 rpm and 55° C. to obtain a carbon fiber / zinc salt solution; the pH of the carbon fiber / zinc salt solution is adjusted to 8.0 by ammonia water (wherein the ammonia concentration is 2 wt %); hexadecyltrimethylammonium bromide and deionized water are mixed in a mass ratio of 0.00025:1, and heated to dissolve at a stirring speed of 1000 rpm and 55° C. to obtain an organic ammonium salt solution; an equal volume of the obtained organic ammonium salt solution is added to the carbon fiber / zinc salt solution, reacted at 150° C. for 14 h, and dried in an oven at 80° C. for 12 h to obtain a carbon fiber with grown zinc oxide micro-nanostructure.
[0101] (3): Functionalization treatment of carbon fiber surface: 3-aminopropyltriethoxysilane and anhydrous ethanol were mixed in a volume ratio of 23:200, and then 1 mL of deionized water was added. The carbon fiber with the grown zinc oxide micro-nano structure obtained in step (2) was immersed in the mixture and reacted for 12 h at a stirring speed of 800 rpm and a temperature of 80°C. After being taken out, the mixture was washed with anhydrous ethanol for 5 times and dried in an oven at 80°C for 12 h to obtain a modified carbon fiber with surface grafted silanol.
[0102] (4): The modified carbon fiber obtained in step (4) is stirred and mixed with epoxy E51 and 1618 epoxy curing agent in a mass ratio of 1.456:24.09:14.454 at a stirring speed of 1000 rpm for 8 minutes, and then cured at 25°C for 12 hours, 40°C for 8 hours, 60°C for 4 hours, and 80°C for 4 hours to obtain an interface-reinforced carbon fiber composite material.
[0103] The morphology of the modified carbon fiber obtained in this embodiment is as follows: Figure 1 As shown, it can be found that the zinc oxide structure on the surface of the carbon fiber grows uniformly and densely, and the in-situ grown zinc oxide is firmly bonded to the carbon fiber, which can produce a strong mechanical interlocking effect between the carbon fiber and the resin. Then, the functionalized modified molecules on the surface of the carbon fiber introduce amino groups, which have the same groups as the resin curing agent, so that it can react with the epoxy resin to form chemical bonds, which can further enhance the interfacial bonding strength between the carbon fiber and the resin.
[0104] The surface of carbon fiber grows zinc oxide micro-nanostructures and forms an interface mechanical interlocking with the resin. After surface functionalization treatment, the chemical bond between the surface and the resin forms a chemical bonding reinforcement. The synergistic effect of mechanical interlocking and chemical bonding reinforcement comprehensively improves the macroscopic performance of carbon fiber composites. The friction and wear test measured that the wear rate of the composite material was reduced by 45%, the multiphase flow erosion test measured that the erosion mass of the composite material was reduced by 25%, and the erosion volume loss was reduced by 20%. Then, under a scanning electron microscope (such as Figure 2 (As shown in the figure) After the erosion test, the interface between carbon fiber and epoxy resin was observed. It was found that the carbon fiber and epoxy resin were tightly bonded at the interface, and the stress was evenly transferred to the surface of the carbon fiber, indicating that the composite material with synergistic effect of mechanical interlocking and chemical bonding at the interface has excellent anti-erosion and anti-wear properties.
[0105] Example 2
[0106] (1) Pre-growth of seed layer on carbon fiber surface: The pre-treated carbon fiber powder was added to a mixture of sodium hydroxide and zinc acetate dihydrate (the mass ratio of sodium hydroxide to zinc acetate dihydrate was 1:2.5), and a hydrothermal reaction was performed at a stirring speed of 300 rpm and a temperature of 150° C. for 14 h, and then cooled to room temperature. The step of “heating again for hydrothermal reaction and cooling to room temperature” was repeated for a total of 3 times to obtain a carbon fiber with a zinc oxide seed layer grown on the surface;
[0107] (2) Growth of zinc oxide micro-nanostructure on carbon fiber surface: The carbon fiber with the surface grown zinc oxide seed layer obtained in step (1) and zinc nitrate hexahydrate were mixed in 20 mL of deionized water at a mass ratio of 0.5:0.33, and heated to dissolve and disperse at a stirring speed of 1000 rpm and 55° C. to obtain a carbon fiber / zinc salt solution; the pH of the carbon fiber / zinc salt solution was adjusted to 8.35 with ammonia water (wherein the ammonia concentration was 10 wt %); hexadecyltrimethylammonium bromide and deionized water were mixed in a mass ratio of 0.00025:1, and heated to dissolve at a stirring speed of 1000 rpm and 55° C. to obtain an organic ammonium salt solution; an equal volume of the obtained organic ammonium salt solution was added to the carbon fiber / zinc salt solution, reacted at 150° C. for 14 h, and dried in an oven at 80° C. for 12 h to obtain a carbon fiber dry with grown zinc oxide micro-nanostructure.
[0108] (3) Surface functionalization of carbon fiber: 3-aminopropyltriethoxysilane and anhydrous ethanol were mixed in a volume ratio of 23:400, and then 5 mL of deionized water was added. The carbon fiber with the grown zinc oxide micro-nano structure obtained in step (2) was immersed in the mixture and reacted for 12 h at a stirring speed of 800 rpm and a temperature of 80°C. After being taken out, the mixture was washed with anhydrous ethanol for 5 times and dried in an oven at 80°C for 12 h to obtain a modified carbon fiber with surface grafted silanol.
[0109] (4) The modified carbon fiber obtained in step (4) was stirred and mixed with epoxy E51 and 1618 epoxy curing agents in a mass ratio of 1.456:24.09:14.454 at a stirring speed of 1000 rpm for 8 minutes, and then cured at 25°C for 12 hours, 40°C for 8 hours, 60°C for 4 hours, and 80°C for 4 hours to obtain an interface-reinforced carbon fiber composite material.
[0110] The morphology of the modified carbon fiber obtained in this embodiment is as follows: Figure 3 As shown, it can be found that the zinc oxide structure growth on the carbon fiber surface is still relatively uniform and dense, but compared with Example 1, the size of zinc oxide becomes smaller, but the obtained in situ grown zinc oxide and carbon fiber are still firmly combined, so that the carbon fiber and the resin have a strong mechanical interlocking effect, and then, the functionalized modified molecules on the surface of the carbon fiber introduce amino groups, which have the same groups as the resin curing agent, so that it can react with the epoxy resin to form chemical bonds, which can further improve the interface bonding strength between the carbon fiber and the resin.
[0111] The surface of carbon fiber grows zinc oxide micro-nanostructures and forms an interface mechanical interlocking with the resin. After surface functionalization treatment, the chemical bond between the surface and the resin forms a chemical bonding reinforcement. The synergistic effect of mechanical interlocking and chemical bonding reinforcement comprehensively improves the macroscopic performance of carbon fiber composites. The friction and wear test measured that the wear rate of the composite material was reduced by 40%, the multiphase flow erosion test measured that the erosion mass of the composite material was reduced by 23%, and the erosion volume loss was reduced by 18%. Then, under a scanning electron microscope (such as Figure 4 (As shown in the figure) After the erosion test, the interface between carbon fiber and epoxy resin was observed. It was found that the carbon fiber and epoxy resin were still tightly bonded at the interface, and the stress was evenly transferred to the carbon fiber surface, indicating that the composite material with synergistic effect of interface mechanical interlocking and chemical bonding has excellent anti-erosion and anti-wear properties.
[0112] Example 3
[0113] (1) Pre-growth of seed layer on carbon fiber surface: The pre-treated chopped carbon fiber was added to a mixture of sodium hydroxide and zinc sulfate (the mass ratio of sodium hydroxide to zinc sulfate was 1:2.0), and a hydrothermal reaction was performed for 12 h at a stirring speed of 100 rpm and a temperature of 120° C., and then cooled to room temperature. The step of “heating again for hydrothermal reaction and cooling to room temperature” was repeated for a total of 5 times to obtain a carbon fiber with a zinc oxide seed layer grown on the surface;
[0114] (2) Growth of zinc oxide micro-nanostructure on carbon fiber surface: The carbon fiber with the surface growth zinc oxide seed layer obtained in step (1) and zinc chloride were mixed in 20 mL of deionized water at a mass ratio of 0.2:0.29, and heated to dissolve and disperse at a stirring speed of 500 rpm and 40° C. to obtain a carbon fiber / zinc salt solution; the pH of the carbon fiber / zinc salt solution was adjusted to 7.5 with ammonia water (wherein the ammonia concentration was 10 wt %); tetraethylammonium sulfate and deionized water were mixed in a mass ratio of 0.00025:1, and heated to dissolve at a stirring speed of 500 rpm and 40° C. to obtain an organic ammonium salt solution; an equal volume of the obtained organic ammonium salt solution was added to the carbon fiber / zinc salt solution, reacted at 120° C. for 12 h, and dried in an oven at 60° C. for 12 h to obtain a carbon fiber dry with a zinc oxide micro-nanostructure.
[0115] (3) Surface functionalization of carbon fiber: N-β-aminoethyl-γ-aminopropyltrimethoxysilane and anhydrous ethanol were mixed in a volume ratio of 23:200, and 1 mL of deionized water was added. The carbon fiber with the grown zinc oxide micro-nano structure obtained in step (2) was immersed in the mixture and reacted for 15 h at a stirring speed of 500 rpm and a temperature of 60 ° C. After being taken out, it was washed with anhydrous ethanol for 3 times and dried in an oven at 60 ° C for 12 h to obtain a modified carbon fiber with surface grafted silanol.
[0116] (4) The modified carbon fiber obtained in step (4) was stirred and mixed with epoxy E44 and 1618 epoxy curing agents in a mass ratio of 1.456:24.09:14.454 at a stirring speed of 1000 rpm for 8 minutes, and then cured at 25°C for 12 hours, 40°C for 8 hours, 60°C for 4 hours, and 80°C for 4 hours to obtain an interface-reinforced carbon fiber composite material.
[0117] The interface-reinforced carbon fiber composite material prepared in this embodiment also exhibits excellent effects.
[0118] Example 4
[0119] (1) Pre-growth of seed layer on carbon fiber surface: Add the pre-treated carbon fiber powder to a mixture of sodium hydroxide and zinc nitrate (the mass ratio of sodium hydroxide to zinc nitrate is 1:2.3), perform hydrothermal reaction for 12 h at a stirring speed of 200 rpm and a temperature of 130° C., cool to room temperature, and repeat the step of “heating again for hydrothermal reaction and cooling to room temperature” for a total of 2 times to obtain a carbon fiber with a zinc oxide seed layer grown on the surface;
[0120] (2) Growth of zinc oxide micro-nanostructure on carbon fiber surface: The carbon fiber with the surface grown zinc oxide seed layer obtained in step (1) and zinc chloride were mixed in 20 mL of deionized water at a mass ratio of 0.3:0.30, and heated to dissolve and disperse at a stirring speed of 8000 rpm and 65° C. to obtain a carbon fiber / zinc salt solution; the pH of the carbon fiber / zinc salt solution was adjusted to 9.0 with ammonia water (wherein the ammonia concentration was 10 wt %); alanine dimethylamine salt and deionized water were mixed in a mass ratio of 0.00025:1, and heated to dissolve at a stirring speed of 8000 rpm and 65° C. to obtain an organic ammonium salt solution; an equal volume of the obtained organic ammonium salt solution was added to the carbon fiber / zinc salt solution, reacted at 130° C. for 10 h, and dried in an oven at 90° C. for 8 h to obtain a carbon fiber dry with grown zinc oxide micro-nanostructure.
[0121] (3) Surface functionalization of carbon fiber: N-(2-aminoethyl)-3-propylaminomethoxymethylsilane and anhydrous ethanol were mixed in a volume ratio of 23:300, and 3 mL of deionized water was added. The carbon fiber with the grown zinc oxide micro-nano structure obtained in step (2) was immersed in the mixture and reacted at a stirring speed of 700 rpm and a temperature of 75°C for 8 h. After being taken out, the carbon fiber was washed with anhydrous ethanol for 4 times and dried in an oven at 90°C for 8 h to obtain a modified carbon fiber with surface grafted silanol.
[0122] (4) The modified carbon fiber obtained in step (4) was stirred and mixed with epoxy E44 and 1618 epoxy curing agents in a mass ratio of 1.456:24.09:14.454 at a stirring speed of 1000 rpm for 8 minutes, and then cured at 25°C for 12 hours, 40°C for 8 hours, 60°C for 4 hours, and 80°C for 4 hours to obtain an interface-reinforced carbon fiber composite material.
[0123] The interface-reinforced carbon fiber composite material prepared in this embodiment also exhibits excellent effects.
[0124] Comparative Example 1
[0125] Compared with Example 1, in this comparative example, only the pretreatment operation in step 1 is performed on the carbon fiber, and the relevant parameter conditions are the same as those in Example 1.
[0126] The morphology of the modified carbon fiber obtained in this comparative example is as follows Figure 5 As shown in the figure, it can be found that the surface of the carbon fiber is smooth, but it is slightly etched due to the nitric acid treatment. Although hydroxyl / carboxyl groups are introduced into the surface, the surface activity is still low and the bonding strength with the resin is poor.
[0127] The friction and wear test showed that the wear degree of the pre-treated carbon fiber composite material was much more serious than that of Example 1. The multiphase flow erosion test showed that the erosion volume loss of the in-situ reinforced carbon fiber composite material with zinc oxide seed layer increased. Figure 6 (As shown in the figure) After the two tests were completed, the interface between the carbon fiber and the epoxy resin was observed, and it was found that the carbon fiber and the epoxy resin were poorly bonded at the interface, the stress was not evenly transmitted, and the carbon fiber itself was broken, indicating that the technology of the present application improves the erosion resistance and wear resistance of the carbon fiber reinforced composite material through the synergistic effect of interface mechanical interlocking and chemical bonding.
[0128] Comparative Example 2
[0129] Compared with Example 1, this comparative example only removes the step of growing the seed layer in step (1) (the pre-treatment is still retained), and the other method steps are the same.
[0130] The morphology of the modified carbon fiber obtained in this comparative example is as follows Figure 7 As shown, it can be found that zinc oxide structure grows on the surface of carbon fiber, but the growth is sparse and uneven. Most zinc oxide cannot grow on the surface of carbon fiber. Although hydroxyl / carboxyl groups are introduced into the surface due to pre-treatment, the surface activity is low, and there is only mechanical interlocking effect with the resin, and the bonding strength with the resin is poor.
[0131] The friction and wear test showed that the wear rate of the carbon fiber composite material obtained in Comparative Example 2 was reduced by 10%, and the multiphase flow erosion test showed that the erosion mass of the in-situ reinforced carbon fiber composite material with zinc oxide seed layer was reduced by 12.8%, and the volume loss was reduced by 13.5%. Figure 8 (As shown in the figure), after the erosion test was completed, the interface between the carbon fiber and the epoxy resin was observed, and it was found that the bonding between the carbon fiber and the epoxy resin at the interface was improved compared with that in Comparative Example 1, but the bonding was still worse than that in Example 1. Although the expansion of the cracks was blocked, the interface bonding strength was still poor, indicating that the dense and uniform zinc oxide micro-nano structure obtained in the pre-grown seed layer can better enhance the bonding strength between the fiber and the resin, but the interface mechanical interlocking alone is not as good as the synergistic effect of interface mechanical interlocking and chemical bonding in the present application technology to improve the erosion resistance and wear resistance of the carbon fiber reinforced composite material.
[0132] Comparative Example 3
[0133] Compared with Example 1, this comparative example only removes the carbon fiber surface functionalization step in step (3), and the other method steps are the same.
[0134] The morphology of the modified carbon fiber obtained in this comparative example is as follows Fig. 9 As shown, it can be found that zinc oxide structure grows on the surface of carbon fiber, and is neatly arranged, uniformly and densely grown. Compared with the embodiment, no surface functionalization treatment is performed, so there is only a single mechanical interlocking effect with the resin, but the surface roughness of the carbon fiber becomes larger, and the mechanical interlocking effect is stronger than the first two comparative cases.
[0135] The friction and wear test showed that the wear rate of the carbon fiber composite material obtained in Comparative Example 3 was reduced by 33%. The multiphase flow erosion test showed that the erosion mass of the in-situ reinforced carbon fiber composite material with zinc oxide seed layer was reduced by 18.2%, and the volume loss was reduced by 16.5%. Fig.10 (As shown in the figure) After the erosion test was completed, the interface between the carbon fiber and the epoxy resin was observed, and it was found that the bonding between the carbon fiber and the epoxy resin at the interface was better than that of Comparative Examples 1 and 2, but the overall performance was slightly worse than that of Example 1, which further illustrates that the dense and uniform zinc oxide micro-nano structure obtained by the pre-grown seed layer better enhances the bonding strength between the fiber and the resin, and enhances the interface mechanical interlocking effect between the carbon fiber and the resin, but the interface mechanical interlocking alone is not as good as the technology of the present application through the synergistic effect of interface mechanical interlocking and chemical bonding to improve the erosion resistance and wear resistance of carbon fiber reinforced composite materials in many aspects.
[0136] Comparative Example 4
[0137] Compared with Example 1, this comparative example lacks the step of growing the surface zinc oxide micro-nanostructure in step (2), and the rest is the same as Example 1.
[0138] The morphology of the modified carbon fiber obtained in this comparative example is as follows Fig.11 As shown, it can be found that although zinc oxide structure grows on the surface of carbon fiber, the growth is sparse and the morphology is similar to that of comparative example 1. Compared with the embodiment, although the surface functionalization treatment is also carried out, the roughness is lower and the mechanical interlocking effect with the resin is weaker than that of embodiment 1. However, due to the surface functionalization treatment, the bonding effect with the resin is stronger than that of comparative case 1.
[0139] The friction and wear test showed that the wear rate of the carbon fiber composite material obtained in Comparative Example 4 was reduced by 3.4%. The multiphase flow erosion test showed that the erosion mass of the composite material in this case was reduced by 6.3%, and the volume loss was reduced by 7.1%. Fig.12 (As shown) after the erosion test was completed, the interface between the carbon fiber and the epoxy resin was observed, and it was found that the bonding between the carbon fiber and the epoxy resin at the interface was better than that in Comparative Example 1, but the overall performance was worse than that in Example 1, indicating that the growth of a certain size and dense and uniform zinc oxide micro-nanostructure can better enhance the bonding strength between the fiber and the resin, and enhancing the interfacial mechanical interlocking effect between the carbon fiber and the resin has a great effect on enhancing the bonding force between the fiber and the resin. However, neither the single interfacial mechanical interlocking nor the single surface functionalization treatment is as good as the technology of the present application in improving the erosion resistance and wear resistance of the carbon fiber reinforced composite material in many aspects through the synergistic effect of interfacial mechanical interlocking and chemical bonding.
[0140] The friction test wear rate data in Examples 1-2 and Comparative Examples 1-4 are as follows: Fig.13 As shown; the erosion test mass loss data in Examples 1-2 and Comparative Examples 1-4 are as follows Fig.14 As shown; the erosion test volume loss data in Examples 1-2 and Comparative Examples 1-4 are as follows Fig.15 shown.
[0141] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0142] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. A method for preparing modified carbon fiber, characterized in that: include: A zinc oxide seed layer and a zinc oxide micro-nano structure were sequentially constructed in situ on the surface of carbon fiber by a hydrothermal method to obtain a carbon fiber with a zinc oxide micro-nano structure. And, a silane coupling agent is used to perform surface functionalization treatment on the carbon fiber with zinc oxide micro-nano structure to obtain modified carbon fiber.
2. The preparation method according to claim 1, characterized in that: Specifically include: (1) subjecting a first mixed reaction system comprising at least carbon fiber, an alkaline substance, and a zinc salt to a hydrothermal reaction, cooling the system to room temperature, and then heating the system to repeat the hydrothermal reaction and cooling operations to obtain a carbon fiber having a surface growth seed layer; (2) subjecting a second mixed reaction system comprising at least the carbon fiber of the surface growth seed layer, an organic ammonium salt, and a zinc salt to a hydrothermal reaction to obtain a carbon fiber having a zinc oxide micro-nano structure; (3) placing the carbon fiber having the zinc oxide micro-nano structure in a mixed solution comprising a silane coupling agent and a solvent for functionalization treatment to obtain a modified carbon fiber.
3. The preparation method according to claim 2, characterized in that: The carbon fiber includes any one or more combinations of carbon fiber powder, chopped carbon fiber, and carbon fiber cloth; And / or, the alkaline substance includes sodium hydroxide and / or ammonia water; And / or, the zinc salt in step (1) includes any one or more combinations of zinc sulfate, zinc acetate dihydrate, zinc nitrate, and zinc chloride; And / or, the mass ratio of the alkaline substance to the zinc salt in step (1) is 1:(1.8-2.5); And / or, the process parameters adopted in the hydrothermal reaction in step (1) include: temperature of 120-150° C., reaction time of 8-14 h, stirring speed of 100-300 rpm; And / or, the heating, hydrothermal reaction and cooling operations in step (1) are repeated 2 to 5 times.
4. The preparation method according to claim 2, characterized in that: Step (2) specifically includes: The carbon fiber and zinc salt of the surface growth seed layer obtained in step (1) are mixed with water, and heated to dissolve and disperse at a stirring speed of 500 to 1000 rpm and a temperature of 40 to 65° C. to form a carbon fiber / zinc salt dispersion, and ammonia water is used to adjust the pH value of the carbon fiber / zinc salt solution to 7.5 to 9.0; Mixing an organic ammonium salt with water, and heating and dissolving them at a stirring speed of 500 to 1000 rpm and a temperature of 40 to 65° C. to form an organic ammonium salt solution; Furthermore, the organic ammonium salt solution is mixed with the carbon fiber / zinc salt dispersion and reacted at 120-150° C. for 10-14 hours, and then dried to obtain the carbon fiber with zinc oxide micro-nano structure.
5. The preparation method according to claim 4, characterized in that: The mass volume ratio of the carbon fiber, zinc salt and water in the surface growth seed layer is (0.2-0.5) g: (0.29-0.33) g: 20 mL; and / or, the concentration of the aqueous ammonia is 2 to 10 wt %; And / or, the mass ratio of the organic ammonium salt to water is (0.0001-0.0003):1; And / or, the volume ratio of the organic ammonium salt solution to the carbon fiber / zinc salt dispersion is (0.5-1.5):1; And / or, the drying process is carried out at a temperature of 60 to 90° C. and for a time of 8 to 12 hours; And / or, the zinc salt in step (2) includes any one or more of zinc nitrate, zinc chloride and zinc acetate; And / or, the organic ammonium salt includes any one or more combinations of cetyltrimethylammonium bromide, tetraethylammonium sulfate, cetyltrimethylammonium fluoride, and alanine dimethylamine salt.
6. The preparation method according to claim 2, characterized in that: Step (3) specifically comprises: mixing a silane coupling agent, a solvent and water, then adding carbon fiber having a zinc oxide micro-nano structure and reacting for 8 to 15 hours at a stirring speed of 500 to 800 rpm and a temperature of 60 to 80° C., and then washing and drying to obtain a modified carbon fiber; The volume ratio of the silane coupling agent, anhydrous ethanol and water is 23: (200-400): (1-5); the silane coupling agent includes any one or more combinations of Np-aminoethyl-γ-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-propylaminomethoxymethylsilane and 3-aminopropyltriethoxysilane; the drying temperature is 60-90°C and the time is 8-12h.
7. Modified carbon fiber prepared by the preparation method according to any one of claims 1 to 6.
8. A carbon fiber reinforced composite coating, characterized in that: The carbon fiber reinforced composite coating is obtained by mixing the modified fiber according to claim 7, epoxy resin and curing agent and applying the mixture to the surface of the substrate for curing.
9. A carbon fiber reinforced composite material, characterized in that: The carbon fiber reinforced composite material is obtained by mixing the modified fiber according to claim 7, epoxy resin and a curing agent and subjecting the mixture to a curing treatment.
10. Use of the modified carbon fiber according to claim 7, the carbon fiber reinforced composite coating according to claim 8 or the carbon fiber reinforced composite material according to claim 9 in preparing materials for service in marine environments.
Citation Information
Patent Citations
Preparation method of titanium dioxide-silane coupling agent co-enhanced carbon cloth reinforced resin-based friction material
CN108329649A
Preparation method of carbon nanotube-chopped carbon fiber composite modified epoxy coating
CN116355501A
Preparation method for regulating and controlling interface transition layer of carbon fiber reinforced resin composite material
CN117247573A
Cited By
Oxygen-donor modified carbon fiber composites for controlled thermal demisability
WO2026188177A1